The Effect of Good Corporate Governance and Leverage on Company Value Moderated by Profitability in the Coal Sub-Sector - Delia Awaliah; Ferikawita M. Sembiring (Journal of International Accounting, Taxation and Information Systems, 2025)
The aim of this study is to examine the ramifications of robust corporate governance and leverage on firm valuation, with profitability serving as a moderating variable. The inquiry is centred on coal sub-sector enterprises listed on the Indonesia Stock Exchange over the period 2019 to 2023. A quantitative methodology was adopted, employing secondary data, with the sample determined through purposive sampling that produced ten firms. The assessment of data was conducted through Moderated Regression Analysis (MRA) facilitated by the Eviews 10 software. The outcomes demonstrate that managerial shareholding, institutional shareholding, and the presence of independent commissioners exert a favourable effect on firm valuation, while leverage shows no statistically discernible influence. Taken together, managerial shareholding, institutional shareholding, independent commissioners, and leverage display a collective effect on firm valuation. Moreover, profitability is shown to weaken the association between independent commissioners and firm valuation, though it does not moderate the relationships of managerial shareholding, institutional shareholding, or leverage with firm valuation.